2014
DOI: 10.3126/narj.v9i0.11638
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Mulching on Wheat Yield and Weed Floras in the Mid-hills of Nepal

Abstract: Studies on the effect of mulching and weed management strategies in wheat were initiated at Khumaltar during the winter season of 2000-2002. The treatments were weedy check, handweed alone, post emergence application of sulfosufuron, and NPK application together with or without mulching. Rice straw mulch was applied at the rate of 4 t/ha. Phalaris minor, Alopecuros sp., Chenopodium album, Rumex crispus, Polygonum hydropiper, Stellaria media, Cannabis sativa, and Soliva anthemifolia were the dominant species. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 1 publication
2
5
0
Order By: Relevance
“…Higher number of effective tillers m -2 in mulched crop was probably due to soil moisture conservation, weed suppression and organic matter addition in the soil. Similar finding was also reported by Ranjit et al (2009). Number of grains per spike is one of the most crucial yield determining components and has directly related to the grain yield of wheat.…”
Section: Benefit Cost Ratio (Bcr)supporting
confidence: 89%
“…Higher number of effective tillers m -2 in mulched crop was probably due to soil moisture conservation, weed suppression and organic matter addition in the soil. Similar finding was also reported by Ranjit et al (2009). Number of grains per spike is one of the most crucial yield determining components and has directly related to the grain yield of wheat.…”
Section: Benefit Cost Ratio (Bcr)supporting
confidence: 89%
“…Higher effective tillers per square meter was also observed in mulching by Ram et al (2013); Ranjit et al (2014) and Stagnari et al (2014).…”
Section: Yield Attributing Charactersmentioning
confidence: 71%
“…Similarly, significantly taller plant height was observed in mulch plots than non-mulched plots. Dahal et al (2013) and Ranjit et al (2014) also reported positive effect of mulch on plant height due to favourable growing condition. Highest LAI at 60 DAS was produced in 5 th December which was statistically at par with 20 th November and significantly higher than 20 th December.…”
Section: Phenological and Growth Attributesmentioning
confidence: 90%
“…Cannabis Sativa is among the broadleaf weeds. 17 Among 104 weed species belonging to 36 families in the rice field of Kathmandu valley that have medicinal values, the leaf of Cannabis sativa var. indica has been reported to have an antitumor effect.…”
Section: Cannabis As Nepalese Floramentioning
confidence: 99%